Mengungkap Praktik Akuntansi Manajemen Strategik Terhadap Kinerja Keuangan Pada Badan Usaha Milik Desa (Bumdesa) Bhuana Utama Desa Panji - Sari, Corina Metha; Astawa, I Gede Putu Banu (Jurnal Akuntansi Profesi, 2021)
This study aims to reveal strategic management accounting practices on financial performance in the Village Owned Enterprises (Bumdesa) Bhuana Utama Panji Village. Based on the profit and loss report on Bumdesa Panji, which gets a significant increase in profit from year to year, a strategic plan can be made by the Bumdesa management with the aim of maintaining and increasing these profits in the future. This research is a qualitative descriptive study with the methods used are observation, interviews, and document analysis. The results obtained in this study that strategic management accounting can be used by a business entity in conducting analysis to increase profits in its business.Keywords: Strategic Management Accounting, Financial Performance, Village-Owned Enterprises